Market Orientation, Entrepreneurship Orientation, and Company Performance: Study on Small and Medium Industries (SMES) Furniture in Demak District - Wibisono, Totok; Universari, Nuria; Budiati, Yuli (Economics and Business Solutions Journal, 2020)
The objectives of this research were to examine the effect of market orientation and entrepreneurial orientation toward firm performance. The populations of this study were small and medium enterprises (SMEs) in Demak regency. The sample were the furniture industry SMEs. This is a survey type of questionnaire based research. Sample size of the study is 86 and the data collection technique with purposive sampling. The data analysis used was PLS (Partial least Square). The research result showed that market orientation and entrepreneurial orientation have a positive effect on firm performance. It was evident that market orientation and entrepreneurial